Meta-analysis of studies on protection provided by different prophylactic agents, their routes of administration and incubation times against nodavirus infection in Macrobrachium rosenbergii - Chen, Ken Fong; Maran, Sathiya; Tan, Wen Siang; Ong, Lin Kooi; Zainal Abidin, Syafiq Asnawi; Othman, Iekhsan; Tey, Beng Ti; Lee, Ronald Fook Seng (Elsevier, 2022)
White tail disease caused by Macrobrachium rosenbergii nodavirus (MrNV) and extra small virus (XSV) is an infection that primarily affects giant freshwater prawns, Macrobrachium rosenbergii, which in turn causes significant economic losses in aquaculture farms worldwide. In response, different prophylactic agents have been studied to improve resistance to this infection. This meta-analysis aims to assess the effectiveness of different prophylactic agents in promoting shrimp survival. Embase, Google Scholar, PubMed, and Scopus search engines were used to search for relevant articles from 2000 to 2022. Articles were screened to only select articles studying crustaceans being given prophylaxis before the disease challenge. Treatments were analyzed on overall survival, and we performed subgroup analysis of treatment type, administration routes, treatment incubation time pre-infection, and whether the prophylactic agents were derived from MrNV, XSV, or a mixture of both. Between the 3 major prophylaxis types, DNA/RNA prophylaxis, viral protein-based prophylaxis, and supplements, all conferred protection against MrNV infection, though no differences between groups were observed. A shorter incubation period (≤ 7 days) conferred better protection, and prophylactic agents from MrNV origin were found to be more effective. A high degree of heterogeneity was detected between studies, necessitating future large-scale studies addressing possible bias.